2011
DOI: 10.1021/mp200092v
|View full text |Cite
|
Sign up to set email alerts
|

The Subcellular Distribution of Small Molecules: From Pharmacokinetics to Synthetic Biology

Abstract: The systemic pharmacokinetics and pharmacodynamics of small molecules are determined by subcellular transport phenomena. Although approaches used to study the subcellular distribution of small molecules have gradually evolved over the past several decades, experimental analysis and prediction of cellular pharmacokinetics remains a challenge. In this article, we surveyed the progress of subcellular distribution research since the 1960s, with a focus on the advantages, disadvantages and limitations of the variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 148 publications
0
59
0
Order By: Relevance
“…Chemotypes have been identified that improve cellular uptake,(70) including conjugation of polyarginine,(71) as well as those that influence localization. (72) Such data could be incorporated into a traditional medicinal chemistry approach or chemical similarity searching. Interestingly, the permeability(73) and localization of multivalent compounds can be improved by changing the scaffold, in particular the module used to separate RNA-binding modules, and by the RNA-binding module itself.…”
Section: Resultsmentioning
confidence: 99%
“…Chemotypes have been identified that improve cellular uptake,(70) including conjugation of polyarginine,(71) as well as those that influence localization. (72) Such data could be incorporated into a traditional medicinal chemistry approach or chemical similarity searching. Interestingly, the permeability(73) and localization of multivalent compounds can be improved by changing the scaffold, in particular the module used to separate RNA-binding modules, and by the RNA-binding module itself.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have also tracked radiolabeled polyplexes in additional organelles using subcellular fractionation methods. While fluorescence microscopy can be affected by environmental factors, such as pH and temperature 25 , radioactivity can provide substantially increased sensitivity and robustness. Furthermore, the use of radiolabeled compounds allows for mass balance calculations, so that 100% of the material applied to the sample can be tracked.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the sequestration of drugs within intracellular organelles can also affect pharmacokinetics and pharmacodynamics after systemic delivery 13 . Among several known organelle sequestration mechanisms, ion-trapping of drugs within acidic compartments, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Protonation of weakly basic molecules leads to increased solubility and decreased membrane permeability, and promotes retention within lysosomes and endosomes. In the case of lipophilic cations, the electrical potential present across the inner membrane of mitochondria drives accumulation of membrane permeant lipophilic cations into this organelle 1, 3, 6, 7 . Beyond transmembrane pH gradients (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation